La « femme·eux·ze » musique québécoise : La recherche sur les genres, les sexualités et autres pratiques non dominantes en musique au Québec (1874-2022) - Blais-Tremblay, Vanessa (Nouveaux cahiers de recherche, 2023)
C’est là un ouvrage de référence qui présente la recherche sur la musique, les genres et les sexualités, et plus largement la vie musicale non dominante au Québec depuis le dernier quart du XIXe siècle jusqu’à aujourd’hui. Issu des travaux réalisés en 202-2022 par le pôle universitaire DIG! Différences et inégalités de genre dans la musique au Québec (D!G), un réseau interdisciplinaire et intersectoriel qui réunit les chercheur·ses, publics, artistes et autres professionnel·les de la musique qui s’intéressent à cette thématique, l’ouvrage comprend une revue de la littérature et une bibliographie de plus de 800 ressources scientifiques.

Parcours professionnels de musiciennes migrantes : de la théorie à l'expérience. Note de terrain à propos du colloque Femmes musiciennes du monde tenu les 26 et 27 novembre 2021 au Centre des musiciens du monde - Marcoux-Gendron, Caroline; Champagne, Lysandre (La Revue musicale OICRM, 2022)

Louise Campbell. Une médiatrice dans l’être - Bertomeu, Fanny (Revue musicale OICRM, 2020)
Formed as a musician and a clarinetist, Louise Campbell is now a music mediator. Based in Montreal, she practices her profession through several structures and for a wide variety of audiences (schoolchildren, professionals, people with disabilities ...) all around Canada, but mainly in Quebec. In this interview, Louise Campbell recounts her experience as a mediator, her (non)-formation in this profession, as well as many aspects in her practice. With the musical object and the creation at the heart of her workshops, Louise Campbell always seeks to establish a “horizontal” exchange relationship with each person she meets.
Keywords: Louise Campbell; creation; création; music mediation; médiation de la musique; partage; relation; relationship; sharing

“Where You Are Accepted, You Blossom”: Toward Care Ethics in Jazz Historiography - Blais-Tremblay, Vanessa (Jazz & Culture, 2019)

Jazz, gender, historiography: a case study of the "Golden Age" of jazz in Montreal (1925-1955) - Blais-Tremblay, Vanessa (Université McGill, 2018)
This dissertation maps the interaction between jazz, identity, modernity and nation during the so-called "golden age" of jazz in Montreal (1925-1955). Drawing on the fields of musicology, women's studies (black feminist theory and feminist research methods in particular), critical dance studies, and cultural studies, this project provides a critical re-writing of the history of Montreal jazz, one which acknowledges various roles that racialized and ethnicized women played in the shaping of modern identities, pleasures and sounds in Quebec. Montreal's particular status as a "showtown" makes it a rich laboratory to study the collaborative creative relationships between jazz music and dance on the black variety stage in the first half of the twentieth century. I also map the specific parameters that articulate the discursive relationship between jazz and vice, in particular as these relate to the gendered and racialized embodiment of morality in interwar Quebec. Finally, this dissertation produces the first extensive biographical accounts and critical listening of several prominent Montreal-based female jazz artists, including pianists Vera Guilaroff and Ilene Bourne, all-girl groups such as The Spencer Sisters and the Montreal Melody Girls Orchestra, black women performers such as Tina Baines Brereton, Bernice Jordan Whims, Marie-Claire Germain, Mary Brown, Natalie Ramirez, as well as piano teacher Daisy Peterson Sweeney and dance teachers Ethel Bruneau and Olga Spencer Foderingham.

A Rich Musical Legacy from Québec: Baroque Motets of the Ursuline and Hôtel-Dieu Monasteries of New France - MacIsaac, Elizabeth Kathleen Norah (Université de Washington, 2018)
Carefully preserved in the archives of the Ursuline and Hôtel-Dieu Monasteries of Quebec are several manuscripts containing Canada’s first sacred works for female voices. The manuscripts contain dozens of intricate motets composed in the French Baroque style, a repository of music which has not been sung for hundreds of years. These motets form a neglected part of Canada’s musical heritage which is waiting to be unearthed and explored. Ursuline and Augustinian nuns arrived to the French territories of the New World to educate and evangelize young women. Singing formed a core element of their teaching and worship. For over one hundred years (1639-1760), church music provided a backbone to Canada’s vibrant musical culture. When the French territories were lost to Britain and Spain, musical culture shifted radically and the sacred French music simply faded into obscurity. An overview of the sweeping events of the French Baroque era includes discussion of France’s social conditions, the political and religious climate, the flowering of the arts and the exploration of the New World. In France, the seventeenth and eighteenth centuries were a time of great strife which heralded the massive social changes to come in the nineteenth century. France’s struggles directly impacted the colony of New France, including that of its religious institutions and music. This study traces the musical activities in the Ursuline community of New France as the nuns lived their mission on the frontier, teaching Aboriginal and colonial girls. The evolution of female emancipation stemming from religious evangelism is considered. Examination of a trove of 160 motets located in the female monasteries of Québec City reveals the high caliber of music practiced by the nuns. No interpretive editions for performance purposes exist. Newly transcribed works have been generated from the manuscripts, with period performance guidance for appropriate ornamentation and ensemble requirements. An in-depth discussion of New France Baroque vocal and choral musical styles is provided, with reference to historical records of how it was taught, as described in contemporaneous music treatises and many original documents specific to these religious female communities.

Femmes et jazz dans le Québec de l’entre-deux-guerres : entre le récit historique, les archives et le passé - Blais-Tremblay, Vanessa (Les Cahiers de la Société québécoise de recherche en musique, 2017)
Cet article porte sur les rôles que les femmes ont joué dans le développement d’une scène jazz à Montréal. Les archives témoignent de l’importance des pianistes Vera Guilaroff et Ilene Bourne, de l’enseignante de piano Daisy Peterson Sweeney, des enseignantes de danse Olga Spencer Foderingham et Ethel Bruneau, ainsi que des danseuses de variétés dans le développement de la plus grande scène jazz du Canada au cours de la première moitié du xxe siècle. Cet article contextualise la présence des femmes dans ces espaces performantiels précis (le piano, l’enseignement, la danse) et explore les processus historiographiques liés à leur exclusion des récits historiques.

Bilan et perspectives sur la situation des compositrices au Québec : vers un décloisonnement des identités - Tremblay, Vicky (Les Cahiers de la Société québécoise de recherche en musique, 2017)
In the field of composition in Quebec, women composers are still less numerous than men composers. While the profession of composer has difficulty being recognized in Quebec society, women composers are twice as marginalized. Many of give evidence to the challenges they face when it comes to integrating into the musical community, and several musicologists have tried to better understand—and eventually solve—the problems specific to women in the field of composition.

Animating the Object: Marcelle Deschênes and acousmatic education in Quebec - Valiquet, Patrick (Organised Sound, 2017)
This article examines the early reception of Pierre Schaeffer’s theoretical work in Quebec through the teaching of Marcelle Deschênes, principal author of the first electroacoustic theory and ear training curricula at both Université Laval and Université de Montréal. An account of Deschênes’s educational career is provided, along with remarks on the contents of her early courses in Morpho-typology and her listening workshops for children, using newly excavated primary material from her private archives. While existing scholarship presumes that Schaefferian thinking arrived in Quebec with the ‘orthodox’ acousmatic approach of Francis Dhomont, this article asserts that a pluralist and multidisciplinary interpretation of Schaeffer’s work can be discerned which pre-dated Dhomont’s teaching and has had an equally lasting impact overall. A methodological argument is also made for including education and other forms of ‘reproductive labour’ in the history of electroacoustic music.

Providing the Taste of Learning: Nadia Boulanger’s Lasting Imprint on Canadian Music - Boivin, Jean (Intersections: Canadian Journal of Music / Intersections : revue canadienne de musique, 2013)
This article traces the rich Canadian legacy of the twentieth-century French musical legend Nadia Boulanger (1887–1979). Through teaching her more than seventy Canadian students, both French- and English-speaking, the renowned French pedagogue played a crucial role in the development of concert art music in this country from the 1920s, notably in Montreal and Toronto. Her numerous Canadian students went on to distinguish themselves as composers, teachers, performers, musicologists, theorists, administrators, and radio producers. Drawing on extensive archival and primary research, this study demonstrates the decisive impact Boulanger had on the development of musical styles and compositional practices in Canada in the last century.

Maryvonne Kendergi (1915-2011) : hommage et mémoire - Bail, Louise (Circuit, 2012)

Life notations of Daisy Sweeney: reflections of othermothering, musicianship and Montreal - Campbell, Arlene (Université York, 2012)
The life story of Mrs. Daisy Sweeney, an African Canadian native of Montreal, Quebec, helps fill a void in the historical documentation of Montreal Blacks (especially female elders). Of particular significance is her prominence as a music educator and othermother during her life. The current literature on African Canadian othermothering experiences is not synonymous with both White or African American females and inclusion of their voices in academic, as well as mainstream spaces, is virtually non-existent. This dissertation asks: What did it mean to be a first generation 'Negro' working class bilingual female in a largely hostile White francophone Quebec metropolis in the early 20th Century? How can her narratives help shape and inform life history and African Canadian othermothering research? My sojourn with Mrs. Daisy Sweeney referenced African centered epistemology in my conceptual understanding of herself and community mothering. Capturing her conversations meant engaging with multiple methodologies articulated through African oral traditions, life history, archival canons and interdisciplinary inquiries. It is striking to note that there were not only certain tensions associated with memory loss and physical limitations (prompted by the aging process) that destabilized and enriched our 'interactive' communication, but also revealed a rupture and reversal of the participant/researcher dynamic. In spite of blatant racial discrimination that plagued Montreal's Black communities during that time, Daisy Sweeney fulfilled a life-long dream and taught hundreds of children the canon of classical piano for over 50 years. She lived her voice through her music, finding ways to validate her own identity and empowering others in the process. She used the musical stage as her platform to draw invaluable connections between race, gender, language and social class. Daisy Sweeney's generation of othermothers is dying out and, as the carriers of culture, the urgency to tell their stories must be emphasized. The account respects, reclaims and reflects those voices. It is time to write in African Canadian female elders and diversify the exclusionary genre of life history and archival research.

La réalité socioprofessionnelle des musiciennes au Québec : un engagement vers l’écriture du féminin - Stévance, Sophie (Loin des yeux près du corps. Entre théorie et création,, 2012)

Ethel Bruneau: Montreal’s Rhythm Tap Legend - Lys, Stevens (Dance Collection Danse, 2011)

Francine-Brunel-Reeves : portrait d’une chercheuse atypique ou quand la pratique appelle la recherche... - Bolduc, Marc (Rabaska : revue d'ethnologie de l'Amérique française, 2008)
This article offers a portrait of Francine Brunel-Reeves, an independent researcher who has followed an exceptional course throughout her active life. It begins with a short biography of this artist, perfomer, educator and independant researcher who has split her life between France, Québec and the United States of America. The second section describes the current state of her work and the theoretical approaches that have delineated her research not only in the field of ethnology, but also in anthropology, musicology and mythology.

Une œuvre purement musicale ? Analyse de la spiritualité des Sœurs des Saints Noms de Jésus et de Marie à partir de l’exemple de l’École de musique Vincent-d’Indy - Laperle, Dominique (Études d'histoire religieuse, 2008)
L’École de musique Vincent-d’Indy des Soeurs des Saints Noms de Jésus et de Marie (connue avant 1951 sous le nom d’École supérieure de musique d’Outremont) fut considérée comme l’une des meilleures du genre dans la province de Québec. Cette réputation ne peut passer sous silence le fait qu’il s’agisse d’une institution catholique. Dans la vie scolaire quotidienne, quelle place occupait réellement la spiritualité ? En étudiant les Constitutions, le Coutumier, les programmes musicaux, les lettres circulaires et différents imprimés des religieuses, nous pouvons mieux identifier la spiritualité à laquelle se rattache cette communauté et comprendre comment elle l’a vécue et partagée.

Itinéraire de quatre pionnières de la vie culturelle à Québec après 1945 - Harvey, Fernand (Les cahiers des dix, 2007)
À Québec comme partout ailleurs, la place des femmes dans la sphère publique est relativement récente. L’idée qu’une femme puisse poursuivre des études universitaires, travailler à l’extérieur de la maison ou entreprendre une carrière après le mariage a commencé à se généraliser peu avant les années 1960. Dans ce long cheminement, certaines femmes ont joué un rôle pionnier. Cet article examine le parcours de vie de quatre de ces femmes qui ont réussi à faire leur marque dans le milieu culturel et médiatique de la ville de Québec au cours des années qui ont suivi la seconde guerre mondiale : Francoise Larochelle-Roy, Simone Bussières, Georgette Lacroix et Monique Duval. L’itinéraire biographique de ces pionnières permet de mieux comprendre les singularités de leur insertion dans le milieu culturel et professionnel, en même temps que les points communs qui les relient toutes quatre au contexte d’une époque. On les suivra donc depuis l’enfance jusqu’à la vie adulte où elles évolueront dans l’enseignement, le journalisme, l’animation radiophonique, ainsi que dans le monde des lettres.

In and Out of the Sound Studio: Introduction - McCartney, Andra; Waterman, Ellen (Intersections: Canadian Journal of Music / Intersections : revue canadienne de musique, 2006)
Dans l’introduction à ce numéro spécial d’Intersections, Andra McCartney et Ellen Waterman présentent les Dedans et Dehors du Studio, un projet de recherche ethnographique inter-universitaire soutenu financièrement par le CRSH du Canada de 2001 à 2005. L’équipe de recherche a étudié les idées et pratiques des artisans sonores canadiens, se penchant particulièrement sur le sujet de la relative invisibilité et inaudibilité des femmes, réfléchissant aux différentes manières dont les technologies et pratiques sonores peuvent être orientées sexuellement. Dans leurs essais, les auteures discutent des relations trouvées entre les termes genre, son et technologie, du point de vue aussi bien terminologique, qu’esthétique, du mentorat, ou encore méthodologique et théorique. Les contributions de McCartney, Diamond, Laplante, Labrosse, Marsh et Bosma sont ici discutées.

Étude sociologique de la musique actuelle du Québec : le cas des Productions Supermusique et du Festival International de Musique Actuelle de Victoriaville - Robineau, Anne (Université de Montréal, 2004)
Cette thèse a pour but l’étude sociologique de la musique actuelle au Québec. La musique actuelle est une pratique de création créée en dehors des institutions académiques et des centres de recherche. La professionnalisation de ce milieu artistique est décrite et analysée dans une perspective sociologique en prenant les cas des Productions Supermusique et du label DAME ainsi que du festival International de Musique Actuelle de Victoriaville. L’objectif de cette thèse est d’acquérir une connaissance sur la façon dont s’est développé ce milieu musical des années 70 à aujourd’hui.

New Games in the Digital Playground: Women Composers Learning and Teaching Electroacoustic Music - McCartney, Andra (Feminism & Psychology, 2002)

Le chant et la musique dans les maisons religieuses de femmes à l'époque de Marie Guyart - Hameline, Jean-Yves (Marie Guyard de l’Incarnation. Un destin transocéanique (Tours, 1599-Québec, 1672), 2000)

“Outside in the Machine”: Institutional Experiences and Strategies of Canadian Women Electroacoustic Composers - McCartney, Andra (Ghosts in the Machine: Women and Cultural Policy in Canada and Australia, 1998)

Albertine Morin-Labrecque : pionnière dans le domaine de la pédagogie musicale au Québec au XXe siècle - Simard, France (Études en musique des futur(e)s diplômé(e)s du Département de musique de l'Université du Québec à Montréal, 1996)

Violet Archer: A Bio-Bibliography - Hartig, Linda (Greenwood Press, 1991)

Quel plain-chant pour la Nouvelle-France ? L'exemple des Ursulines - Pinson, Jean-Pierre (Canadian University Music Review, 1991)
S'il est une musique qui fut pratiquée en Nouvelle-France depuis les origines jusqu'au XXe siècle, ce fut bien celle du plain-chant1. Or, ce répertoire se présente comme un reflet souvent exact du plain-chant gallican, de son histoire et de sa pratique. Certes, il lui a fallu s'adapter aux lieux, aux populations et aux coutumes, mais sa répartition géographique, moins complexe qu'en France, et le nombre plus restreint d'institutions et de paroisses permettent une méthode d'approche à peu près contrôlable. Au cours de notre projet de recherche2, nous avons recueilli à travers le Québec des centaines de sources qui tracent un portrait riche de cette pratique. Mieux : au-delà du plain-chant lui-même c 'est en fait le chant baroque français qui s'est conservé longtemps ici, « sous cloche », dans un milieu très conservateur : ce chant de la Nouvelle-France est un beau cas de Performing practice. Parmi toutes les institutions visitées, les Ursulines de Québec et de Trois-Rivières3 constituent une excellente illustration de ce phénomène. Les sources conservées chez elles, classées dans l'annexe bibliographique, présentent une synthèse assez fidèle des sources demeurées en Nouvelle-France, contribuant ainsi à l'élaboration de ce portrait.

La formation professionnelle des filles dans les écoles supérieures de musique tenues par les religieuses, 1926-1960 - Mendez, Manon (Université de Sherbrooke, 1990)

Les Ursulines et la musique - Gréroire-Reid, Claire; V. -Demers, Micheline (Cap-aux-Diamants : la revue d'histoire du Québec, 1989)

Une missionnaire de la musique : Sœur Marie-Stéphane, S.N.J.M. fondatrice de l'école Vincent-D'Indy - Millette, Juliette (Cahier de la Société historique de Montréal, 1982)

Violet B. Archer : une élève canadienne de Bela Bartok - Lenoir, Yves (Institut supérieur d'archeologie et d'histoire de l'art, Université catholique de Louvain, 1980)

L'enseignement de la musique vocale et instrumentale aux Ursulines de Québec de 1830 à 1880 - Pagé, Thérèse (Université Laval, 1975)

L'histoire de la musique de l'Institut des Sœurs de la Charité de Québec - Roy, Marielle (Université Laval, 1968)

Y a-t-il une compositrice en musique au programme ? - Carignan, Nicole; Vincent, Jean Windsow (Musique et pédagogie)